(untitled) (Baghdad Science Journal, 2025)
In this work involved prepared of several new 1-cyclopentene-1,2-dicarboxylimide linked to oxadiazole and benzothiazole moiety were synthesized by two steps: The first step 2-amino-substituted-1,3,4-oxadiazoles and substituted-2-aminobenzothiazole were reaction with 1-cyclopentene-1,2-dicarboxyl anhydride producing N-( 5- substituted-1,3,4-oxadiazole-2-yl)-1-cyclopentene-1,2-dicarboxyl amic acids and N-(Substitutedbenzothiazole-2-yl)-1-cyclopentene-1,2-dicarboxyl amic acids which in turn were dehydrated in the second step via fusion method to afford he desirable N-(5-substituted-1,3,4-oxadiazole-2-yl)-1-cyclopentene-1,2-dicarboxylimides and N-(Substituted benzothiazole-2-yl)1-cyclopentene-1,2-dicarboxylimides respectively. Structures of the prepared compounds were characterized by depending on FTIR, U.V spectral data which were in agreement with the proposed ones. Finally antibacterial activity of some of the prepared new cyclic imides were studied by two types of bacteria and the results showed that the most of the tested imides posses good biological activity against these bacteria.